Winter's Fundamental Selection Theorem: Reply - Winter, Sidney G. (Quarterly Journal of Economics, 1990)
Journal Article Winter's Fundamental Selection Theorem: Reply Get access Sidney G. Winter Sidney G. Winter U. S. General Accounting Office Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 105, Issue 4, November 1990, Pages 1075–1077, https://doi.org/10.2307/2937888 Published: 01 November 1990